Strabismus-related prejudice in 5-6 year-old children - Lukman, H.; Kiat, J. E.; Ganesan, A.; Chua, W. L.; Khor, K. L.; Choong, Y. F. (group.bmj.com, 2010)
Aims There is a general consensus that individuals with conspicuous strabismus are perceived more negatively with respect to physical appearance, personality and capability. Such social biases can potentially lead to social alienation and negative psychosocial development, particularly when experienced at a young age. This study aims to explore young children’s perception of peers with noticeable exotropia. Methods 128 children, 5e6 years old, took part in this cross-sectional within-group study. The sample viewed four paired images of peers with orthotropia and exotropia, and chose the image they LIKED and the image they would SHARE their favourite toy with. All images were created using digital morphing technique. Results Single proportion tests showed that a significantly greater proportion of the sample chose the orthotropic images as the ones they like (z¼5.74, p<0.001) and the ones they would share their favourite toy with (z¼4.90, p<0.001). Phi coefficient analysis further demonstrated an association between the choice to like and the choice to share (4(504)¼0.34, p<0.001). Conclusions Children as young as 5 years old are found to have negative social reactions towards peers with noticeable exotropia. These findings imply that children with noticeable strabismus may be subjected to social alienation at an early age.